Double Limit Pricing - Gerard van der Meijden; Karolina Ryszka; Cees Withagen (Tinbergen Institute, 2015)
We study resource extraction by a non-renewable resource supplier who faces demand from two regions, one of which employs a tax on the imported resource and a subsidy on the available backstop technology, and one that has no environmental policy in place. The resource extraction path possibly contains two limit pricing phases, both in the presence and in the absence of speculators on the market. In the case with speculators, the resource price is continuous. Without speculators, the price jumps upward when demand from the region with climate policy drops to zero. A tightening of climate policies results in lower initial resource consumption; no Weak Green Paradox occurs. Yet, a decrease in the backstop production cost or an increase in the backstop subsidy shorten the overall extraction period, potentially resulting in higher total climate costs in the case without speculators. An analysis of the welfare effects reveals that the regulated region faces differential non-green and green incentives to tighten its climate policies in the two price regimes. We find that, even though climate damages might go down, unilateral policy tightening is possibly detrimental to the regulated region's non-green welfare due to a resource supply shift to the unregulated region.
Keywords: Q31; Q37; 330; limit pricing; non-renewable resource; monopoly; climate change; carbon tax; renewables subsidy